2015
DOI: 10.1016/j.wneu.2015.03.064
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the Management of Hydrocephalic Children in Northern Mozambique

Abstract: Efforts to improve prevention, early diagnosis, treatment, and follow-up are of utmost importance in Mozambique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Studies in Bangladesh by Mukherjee et al 8 Reported ToRCH is a significant cause in Hydrocephalus in intrauterine infection, where commonest age group was 31 to 90 days (45.0%). Mozambique have an incidence of congenital hydrocephalus equivalent to or greater than developed countries and that post-infectious acquired hydrocephalus occurs at even higher rates 9 . Studies conducted in Uganda had demonstrated infection accounting for 60.0% of hydrocephalus cases.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Bangladesh by Mukherjee et al 8 Reported ToRCH is a significant cause in Hydrocephalus in intrauterine infection, where commonest age group was 31 to 90 days (45.0%). Mozambique have an incidence of congenital hydrocephalus equivalent to or greater than developed countries and that post-infectious acquired hydrocephalus occurs at even higher rates 9 . Studies conducted in Uganda had demonstrated infection accounting for 60.0% of hydrocephalus cases.…”
Section: Introductionmentioning
confidence: 99%